2015
DOI: 10.1016/j.jvolgeores.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic plume vent conditions retrieved from infrared images: A forward and inverse modeling approach

Abstract: International audienceWe present a coupled fluid-dynamic and electromagnetic model for volcanic ash plumes. In a forward approach, the model is able to simulate the plume dynamics from prescribed input flow conditions and generate the corresponding synthetic thermal infrared (TIR) image, allowing a comparison with field-based observations. An inversion procedure is then developed to retrieve vent conditions from TIR images, and to independently estimate the mass eruption rate.The adopted fluid-dynamic model is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Here we have shown that the strength of acoustic sources, and the directivity of the associated wavefield, during volcanic explosions can be estimated by inversion of infrasound waveforms, and the erupted volume can be retrieved from analysis of TIR or visual imagery. The strength of the acoustic monopole source time function presented here, in Figure c, is consistent with previous measurements of eruption rates at Santiaguito [ Cerminara et al , ] based on plume modeling and inversion of TIR data. The strength of the dipole function at Santiaguito (Figure b) is about 2 orders of magnitude smaller than values reported for larger Vulcanian explosions at Tunghuraua volcano [ Kim et al , ] and Strombolian explosions at Mount Erebus [ Johnson et al , ].…”
Section: Discussion and Conclusive Remarkssupporting
confidence: 91%
“…Here we have shown that the strength of acoustic sources, and the directivity of the associated wavefield, during volcanic explosions can be estimated by inversion of infrasound waveforms, and the erupted volume can be retrieved from analysis of TIR or visual imagery. The strength of the acoustic monopole source time function presented here, in Figure c, is consistent with previous measurements of eruption rates at Santiaguito [ Cerminara et al , ] based on plume modeling and inversion of TIR data. The strength of the dipole function at Santiaguito (Figure b) is about 2 orders of magnitude smaller than values reported for larger Vulcanian explosions at Tunghuraua volcano [ Kim et al , ] and Strombolian explosions at Mount Erebus [ Johnson et al , ].…”
Section: Discussion and Conclusive Remarkssupporting
confidence: 91%
“…Particle size distributions are currently assessed based on strategies that use satellite data collected in the thermal infrared (Prata and Bernardo, 2009;Cerminara et al, 2015), ground-based disdrometers and radar systems (Gouhier and Donnadieu, 2008;Scollo et al, 2009), and thermal and visible cameras (Chouet et al, 1974;Ripepe et al, 1993;Bombrun et al, 2015). Each of these methods has their own potential and limitations in terms of the size range considered, as well as spatial and temporal resolution, and specific strategies need to be tailored to the type of emission.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters as plume exit velocity and trajectory, mass discharge rates, gas fluxes, gas compositions, and grain size distributions can now be measured in real time using high-speed visual, thermal, infrared and sulfur dioxide cameras [Bani et al 2013, Harris 2013, Bombrum et al 2014, Gaudin et al 2014a, b, Valade et al 2014, Barni et al 2015, Bombrum et al 2015, Cerminara et al 2015, Bombrun et al 2016, Gaudin et al 2016], a combination of thermal camera, weather radar observations and/ or infrasound measurements , De Angelis et al 2016, Vulpiani et al 2016, and open-path Fourier transform infrared (OP-FTIR) spectrometry [La Spina et al 2015, Allard et al 2016. These measurements have highlighted the unsteady nature of these parameters.…”
Section: Volcano Observationsmentioning
confidence: 99%